PENERJEMAHAN BUKU TEMATIK-TERPADU SD/MI KELAS 1: PEMANFAATAN BAHASA DAN SASTRA DAERAH DALAM PENGANTAR PENDIDIKAN KELAS AWAL - Imam Budi Utomo (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2016)
This paper aims to reveal the contribution of the revitalization perspective toward local language and literature in education field in Indonesia. The writer tried to arrange the translation or local language vertion of text-book thematic-integrative based Curriculum 2013 for elementary (class 1). It is expected for the teacher to convey the subject easily in local language. Also, the students (class 1 until 3) are expected to accept the subject easier and to emerge students’ pride to their mother tounge and local literature.